Photocatalytic degradation of neonicotinoid insecticides using sulfate-doped Ag3PO4 with enhanced visible light activity - Lee, Youn Jun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu; Moon, Joon Kwan; Alvarez, Pedro J.J. (Chemical Engineering Journal, 2020)
Visible light-activated photocatalysts offer a promising approach to remove recalcitrant organic contaminants from water without adding chemicals, using free solar energy. In this study, sulfate-doped silver phosphate (SO4-Ag3PO4) was prepared using a simple precipitation method, and its visible light photocatalytic activity against seven neonicotinoid insecticides currently available on the market was evaluated. The characteristics of the photocatalysts were analyzed using diffuse reflectance-UV/visible spectrophotometer measurements and electrochemical impedance spectroscopy analysis. Photocatalytic degradation of all tested insecticides under visible light irradiation was significantly enhanced by SO4 doping, which decreased band gap energy and charge transfer resistance. The apparent first-order rate constant (kapp) with SO4-Ag3PO4 varied depending on the insecticides (0.003–0.432/min), and was at least 5.4-fold faster than that with pristine Ag3PO4, in the order of thiacloprid (TCP) > nitenpyram (NTP) > imidacloprid (ICP) > clothianidin (CTD) > acetamiprid (ATP) > thiamethoxam (TMX) > dinotefuran (DTF). Even after four reuse cycles, SO4-Ag3PO4 maintained over 75% of its initial photocatalytic efficiency. Reactive species trapping experiments indicated that photoinduced electron holes (h+) were the most important oxidant for ICP degradation.
Keywords: Charge transfer resistance; First-order rate constants; Neonicotinoid insecticides; Photo catalytic degradation; Photocatalytic efficiency; Spectrophotometer measurements; Visible light activated photocatalysts; Visible light photocatalytic activity; Neonicotinoid insecticides; Photocatalytic degradation; Photoinduced hole; Sulfate doped Ag3PO4; Visible light photocatalyst